2013
DOI: 10.5006/0950
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Pseudo-Passivation of Mild Steel in CO2 Corrosion

Abstract: The iron carbonate corrosion product layer formed on mild steel in carbon dioxide (CO 2 ) environments is known to retard corrosion. When not fully covering the steel surface, it may also lead to initiation of localized corrosion, due to a galvanic effect. In this work, the stability of a protective iron carbonate layer has been studied at 80°C over a relatively wide range of bulk pH. Experiments were done in a glass cell using a threeelectrode system. Electrochemical techniques such as linear polarization res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 12 publications
4
38
0
Order By: Relevance
“…8 where polarization resistance efficiency was increased up to 60%. These results are accordance with the EIS result and also indicate that precipitation on the WE slows down the easy transfer of corrosion products and reactant from bulk solution to WE surface [34].…”
Section: Resultssupporting
confidence: 93%
“…8 where polarization resistance efficiency was increased up to 60%. These results are accordance with the EIS result and also indicate that precipitation on the WE slows down the easy transfer of corrosion products and reactant from bulk solution to WE surface [34].…”
Section: Resultssupporting
confidence: 93%
“…Once Fe 2+ and CO 3 2 − are present at the steel/solution interface at sufficiently high concentrations, which make the product of [Fe 2+ ] × [CO 3 2 − ] exceed the solubility product of FeCO 3 , precipitation and crystal growth will occur [26], as described in Equation (11):Fe 2+ + CO 3 2 − → FeCO 3 .…”
Section: Discussionmentioning
confidence: 99%
“…This is attributed to the relatively high CO 2 partial pressure and high pH in the experimental environment. The CO 2 partial pressure in each condition was up to 2.25 MPa, and the pH in corrosive solution was 7.0, which favored the formation of FeCO 3 [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Significant increase in open circuit potential and a decrease of the corrosion rate were observed at pH 8, owing to the formation of a mixed film of FeCO 3 and magnetite (Fe 3 O 4 ). Li et al reported that the pseudopassivation could not be achieved at pH 5.6 [19]. At pH 3, the scale is mainly constituted by siderite, which does not promote a passive or pseudopassive state.…”
Section: Effect Of the Scale On Polarization Curve Of Steel In Acidmentioning
confidence: 99%